If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -4a + -6a = 11 Combine like terms: -4a + -6a = -10a 1 + -10a = 11 Solving 1 + -10a = 11 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -10a = 11 + -1 Combine like terms: 1 + -1 = 0 0 + -10a = 11 + -1 -10a = 11 + -1 Combine like terms: 11 + -1 = 10 -10a = 10 Divide each side by '-10'. a = -1 Simplifying a = -1
| (8x-12)=(3x+28) | | -30=6x+4(-x-4) | | 6=-6+4x+2x | | (y+8)=6.333 | | 15+(5-x)=30 | | 5y+2=0.50(10y+4) | | 3y-3+y+53=6y+50-4y | | -4x2/7 | | 4(x+6)=31+3r | | 20+4k=k | | 17/3+6 | | y=6(4)+(-12) | | (6x-14)=(3x+5) | | 3x^2+28x+19=0 | | 3-k-4=3 | | x/(x+600)=0.7 | | x/2+25=50 | | (3+-4)-5= | | 15(x-3)+3x=6(3x+5)-11 | | 7x+w=21y | | -6p+4+p=14 | | 2.25-6p=2.25 | | 3/4r-1/3=5/2 | | 2(2x+9)+3x=4 | | -12=k-6+5k | | y^4+13y^3+40y^2=0 | | 8x-4=3x+15.25 | | 7+3x=-7x-57 | | M=7-3*-2 | | 16-(-4+9)= | | 14b-2=19b+32 | | 21b-17b= |